Pengambilan Keputusan Orang Tua dalam Pemilihan Sekolah Bagi Anak - Diani, Fatma Ulfa; Dewi, Rahmia; Amalia, Ika (Jurnal Psikologi Terapan, 2021)
The purpose of this study is to describe parents' decision-makingin choosing children's schools. This study uses a descriptive quantitative approach with univariate analysis, aimed at describing the situation of parents' decision-making in choosing a child's school without comparison or association with other variables. Data obtained from Swhen Pengambilan Keputusan parents in choosing a child's school. The subjects of the study were eighty parents who chose a school for their child by taking samples using the total sampling technique. The results of the analysis of research data concluded that: the commitment stage has the  highest  percentage in measuring parental decision-making variables in the selection of schools for children; parents who are in early adulthood have a higher percentage of decision-making than parents who are of intermediate adulthood;  parents who have the last D3 education have the highest percentage of decision-making in school selection for children compared to others; parents who  have children in grade 3 have a higher percentage of decision-making than parents in school selection for children in grades 1 and 2.